Analisis Manajemen Pengeluaran Publik dalam Standar Pelayanan Minimal Bidang Pendidikan di Kota Bukittinggi - Nabilla Nabilla; Roni Ekha Putera; Hendri Koeswara (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
This study aims to analyze the management of public expenditure stages carried out by the City Government of Bukittinggi in fulfilling services and improving the quality of basic services for Minimum Service Standards (SPM) in the field of education in the 2022 Fiscal Year. With a budget of more than 181 billion, the City Government of Bukittinggi allocates activity budgeting 80% for basic services and 20% for achieving quality basic services, in Early Childhood Education, Basic Education and Equality/Non-Formal Education. In 2022 the city government is synergizing to further improve the quality of education after the Covid-19 situation by launching a number of new programs in the Bukittinggi Government Featured Program (PUPB). This study then analyzes the stages of public expenditure management carried out by the City Government of Bukittinggi based on the thoughts of Cheryl Williamson Gray. Using a descriptive qualitative research method based on the main data of observation, interviews and other document data as supporting secondary data. The results of the study then show that the City Government of Bukittinggi for the 2022 Fiscal Year has met the service performance target at Minimum Service Standards at 97% with 3% of the deficiencies being mostly in the category of educators and education staff who are still not fully qualified S1/D-IV in each level of education.